Os Clubes de Clientes em Portugal: O Caso do Vinho - Ferreira, Paulo Alexandre Tomás (2007)
This study was performed in the scope of the Marketing Master Degree of the University of Porto - School of Economics, and its purpose is to analyse, to the particular case of wine, and in the context of a national retail operator, the members versus non-members (usually wine clients at that operator stores, who were identified through their loyalty card records analysis) profiles of this company customers club. Based on literature review and on depth interviews, determinant factors characterizing customers profiles were identified, in order to cluster them according to a defined set of characteristics. Investigation hypotheses were tested through statistic models. Afterwards, an inquiry for a customer s representative sample of 150 members and 100 non-members of the studied / target wine club was carried out. Based on achieved results, considering members and non-members specific characteristics identification, we are able to underline the importance of a new differentiating strategic approach on wine production and / or commerce, as well as to generate a set of performance suggestions in order to: - meet customers satisfaction and match their group needs and preferences levels; - develop lasting and reciprocal relationships with their customers, based on a continuous knowledge process; - influence and create loyal customers through exclusive benefits, with real and true value perceived by them.